A study on reward system impact towards employee's motivations: a case study of RISDA Seremban Branch / Nur Fathin Bashirah Zaharudin - Zaharudin, Nur Fathin Bashirah (2017)
The main purposed of the research was to analyse the impact of rewards system on the employee motivation at RISDA Seremban Branch. The specific objective of the study were to study the relationship between rewards system (Extrinsic rewards and intrinsic rewards) towards employee motivation and to identify the most influence factor of rewards system towards employee motivation at RISDA organization. The current research has adopted quantitative approach of analysing the result of the study. The quantitative data was collected through primary survey questionnaires that were distributed among 40 employee. SPSS software was used to analyse the collected data in which frequency analysis, correlation analysis and regression analysis were performed. In addition, the technique of manual thematic analysis was used in order to interpret the information that was gathered through the interview survey.